Tinzaparin for venous thromboembolism in patients with renal impairment: a single‐centre, prospective pilot study. Issue 1 (5th December 2022) - Yeung, James; Dix, Caroline H. K.; Ritchie, Angus G.; Kow, Marian; Chen, Vivien M. Y.
Abstract: Background: Low molecular weight heparins (LMWH) are used extensively for prophylaxis and treatment of venous thromboembolism (VTE), bridging therapy for warfarin and standard of care in cancer‐associated VTE (CA‐VTE). Tinzaparin has the highest molecular weight of all LMWH and relies least on renal clearance to Cockcroft‐Gault creatinine clearance (CrCl) of 20 mL/min. Previous pharmacological studies have demonstrated safety and effectiveness in elderly patients. Prospective clinical trials have confirmed these findings to CrCl 20 mL/min and in CA‐VTE. We describe the pilot program developed at Concord Repatriation General Hospital for tinzaparin. Aims: We aim to confirm the deliverability of tinzaparin in patients with renal insufficiency. Methods: Twenty patients were established on tinzaparin as therapeutic anticoagulation with CrCl or CKD‐EPI estimated glomerular filtration rate (eGFR) 20–50 mL/min with an indication for anticoagulation. Tinzaparin was given as a subcutaneous injection at 175 units/kg as a single daily dose, rounded to the nearest vial size. Tinzaparin anti‐Xa levels were tested at Days 2, 7 and 14 (±1 day) and transition to oral anticoagulants were allowed at clinician discretion. Results: No accumulation of tinzaparin was seen into Day 14. Two patients required dose‐adjustment, five patients had bleeding complications (two major, three minor) and four patients died during follow‐up, all attributable to patients' comorbidities. CrCl and body surface area‐standardised CrCl were significantly correlated with tinzaparin anti‐Xa level only on Day 2, and this effect was lost when patients with CrCl >50 mL/min were excluded. Data from our cohort confirm the deliverability of therapeutic tinzaparin in patients with CrCl or CKD‐EPI eGFR 20–50 mL/min. Bleeding and death outcomes were also comparable to other trials using tinzaparin in CA‐VTE. Conclusion: For patients with renal insufficiency, tinzaparin represents an attractive alternative anticoagulant with once‐daily administration in a range of potential indications.